Development of Flipbook-Based Learning Media for Short Story Texts in 10th Grade at Madrasah Aliyah Negeri 1 Tebo - Salahuddin, Amar; Marlianda, Rendi; Riola, Arsinta (The Future of Education Journal, 2025)
This study aims to develop a learning media using Flipbook media for short story text material. The researcher chose Flipbook media because it is easy to use for the learning process to be interactive and interesting which provides students with an experience like reading a real book with an interactive page turning effect because Flipbook as a visual and multimedia that can contain text, images, and animation. This media was developed to involve the presentation of material in a structured manner, encourage independent learning, be environmentally friendly, cost-effective, make students interested in the learning process and make learning more interesting. This research method is development research or R&D with a 4D model consisting of the stages of defining (define), designing (design), developing (development), and disseminating (disseminate). This research was conducted at Madrasah Aliyah Negeri 1 Tebo in the 2024/2025 academic year, the research subjects were 20 class X students. Data collection techniques used student response questionnaires, teacher responses, media expert validation sheets, language experts, and material experts. The results of this study indicate that researchers produce Flipbook-based learning media as a learning medium for short story text material, the media is said to be valid, seen from the results of the media expert validation obtained a score of 97.3% and is included in the "very valid" category, the language expert validation obtained a score of 95% and is included in the "very valid" category, and the material expert validation obtained a score of 98.3% and is included in the "very valid" category. This means that Flipbook-based learning media is suitable for use by educators and students. The results of the practicality research conducted by educators obtained a score of 96.3% including the "very valid" category, and class X students obtained a score of 98% including the "very valid" category. So it can be concluded that the Flipbook-based learning media that has been developed by researchers is suitable for use, because it has met the valid category.